The Prognostic Value of C-Reactive Protein Serum Levels in Patients with Uterine Leiomyosarcoma - Schwameis, Richard (PLoS One, 2015)
OBJECTIVE: C-reactive protein (CRP) has previously been shown to serve as a prognostic parameter in women with gynecologic malignancies. Due to the lack of valid prognostic markers for uterine leiomyosarcoma (ULMS) this study set out to investigate the value of pre-treatment CRP serum levels as prognostic parameter. METHODS: Data of women with ULMS were extracted from databases of three Austrian centres for gynaecologic oncology. Pre-treatment CRP serum levels were measured and correlated with clinico-pathological parameters. Univariate and multivariable survival analyses were performed. RESULTS: In total, 53 patients with ULMS were included into the analysis. Mean (SD) CRP serum level was 3.46 mg/dL (3.96). Solely, an association between pre-treatment CRP serum levels and tumor size (p = 0.04) but no other clinic-pathologic parameter such as tumor stage (p = 0.16), or histological grade (p = 0.07), was observed. Univariate and multivariable survival analyses revealed that CRP serum levels (HR 2.7 [1.1–7.2], p = 0.037) and tumor stage (HR 6.1 [1.9–19.5], p = 0.002) were the only independent prognostic factors for overall survival (OS) in patients with ULMS. Patients with high pre-treatment CRP serum levels showed impaired OS compared to women with low levels (5-year-OS rates: 22.6% and 52.3%, p = 0.007). CONCLUSION: High pre-treatment CRP serum levels were independently associated with impaired prognosis in women with ULMS and might serve as a prognostic parameter in these patients.